Text-Guided 3D Object Extraction from 360° Tours: A Single-Image Pipeline for Museum Asset Generation - Brandão Filho, Rone C.; Guimaraes, Murilo De Oliveira; Dangoni, Arthur Galdino; Vitória, Arthur Ricardo Sousa; Sousa, Rafael Teixeira; Galvão Filho, Arlindo R. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Currently, many museums are integrating virtual reality into their tours, offering both virtual and mixed reality experiences. This process is still in its early stages, often requiring skilled professionals and time-intensive computational techniques such as photogrammetry to generate good results. In this context, this work presents a streamlined approach that starts from a single 360° panorama and a plain-language prompt, producing a textured 3D model suitable for a VR/AR application. The workflow couples promptable segmentation with recent single-image reconstruction models, eliminating photogrammetry and manual mesh clean-up. Qualitative results on a variety of scenes show that the proposed method delivers visually convincing geometry in well under a minute on a commodity GPU, making large-scale, low-cost digitization practical for institutions of any size. By reducing both human effort and computational overhead, the proposed pipeline produces assets suitable for XR pipelines, which can enable more interactive, immersive, and rapidly updatable museum experiences.